Enzymatic changes in the kidney and brain of freshwater murrel, Channa striatus (Bloch) on short term exposure to sub-lethal concentration of lead nitrate - George, K Roy; Malini, N A; Rajan, Archana; Deepa, R (Indian Journal of Fisheries, 2012)
The effect of short term exposure to sub-lethal concentration (20 ppm) of lead nitrate [Pb(NO3)2] on the activities of alkalinephosphatase, acid phosphatase, succinate dehydrogenase and superoxide dismutase in the kidney and brain of the freshwatermurrel, Channa striatus was studied at 24 and 72 h of exposure. The alkaline phosphatase activity was increased, probablydue to the adverse effect of lead nitrate on the glucose re-absorption and trans-phosphorylation. The decline in acid phosphataseactivity was associated with the tissue damage caused by lead nitrate toxicity. The inhibition of succinate dehydrogenaseactivity indicated impairment of oxidative metabolic cycle and dependence on the anaerobic glycolytic pathway to meet theenergy demands. The reduction in the superoxide dismutase activity revealed an increased oxidative stress on the nervoustissue leading to the lipid peroxidation and damage of brain.